2003
DOI: 10.2105/ajph.93.9.1552
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-Based Differences in Physical Activity: An Environment Scale Evaluation

Abstract: The reliability and validity of self-reported neighborhood environment subscales were supported. Neighborhood environment was associated with physical activity and overweight prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
1,289
9
40

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,586 publications
(1,386 citation statements)
references
References 31 publications
48
1,289
9
40
Order By: Relevance
“…A range of measures were used to identify barriers and motivators for physical activity and sport including the St. Louis Scale -Measuring Physical Activity in Communities [31], Neighbourhood Environment Walkability Scale [32],Environmental Supports for Physical Activity Scale [33] and the Exercise Self-Efficacy Scale [34]. Barriers and motivators were also identified through open-ended questioning in small-group and individual interviews.…”
Section: Methodsmentioning
confidence: 99%
“…A range of measures were used to identify barriers and motivators for physical activity and sport including the St. Louis Scale -Measuring Physical Activity in Communities [31], Neighbourhood Environment Walkability Scale [32],Environmental Supports for Physical Activity Scale [33] and the Exercise Self-Efficacy Scale [34]. Barriers and motivators were also identified through open-ended questioning in small-group and individual interviews.…”
Section: Methodsmentioning
confidence: 99%
“…25 Participants responded to questions about their local area (defined as within a 10-to 15-min walk from home). Responses were scaled from 1 (strongly disagree) to 4 (strongly agree).…”
Section: Outcome Variablementioning
confidence: 99%
“…In addition, as numerous factors contribute to BMI and health outcomes, future research should also take into account variables such as length of residence in the neighborhood. Third, similar to other scales examining neighborhood environments (e.g., streets in my neighborhood [89]), perceived park quality questions could include multiple parks in the respondents' neighborhood, rather than one specific park. However, asking respondents about one particular park may provide stronger associations with that park-specific physical activity, and would also allow for direct comparisons of perceptions and objective measures.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Finally, like other cross-sectional studies, this study lacks a causal explanation for the relationships that were found. Given this, it has been called into question whether physical activity differences are a result of neighborhood design, or if individuals already wishing to engage in physical activity self-select into neighborhoods according to physical activity opportunities [89]. However, a recent study found that even those who did not place a high importance on living near parks are more likely to engage in park-based physical activity when they have greater amount of proximal parkland, indicating that selfselection is not solely the cause of the park-physical activity relationship [90].…”
Section: Limitations and Future Researchmentioning
confidence: 99%